Analysing policies to increase graduate population: do tuition fees matter?. Issue 1 (2nd January 2020) - Cattaneo, Mattia; Civera, Alice; Meoli, Michele; Paleari, Stefano
ABSTRACT: Although broadening equal access to higher education has been an objective public policy for decades, little is known about the effectiveness of alternative means for achieving this goal. Moreover, it has raised a need of explaining the heterogeneity in Higher Education attainment across European countries, where high level of graduate population can be observed both in the presence of high- and low-levels of fees. This paper surveys the extant literature providing some background on the economic concepts of higher education market, and reviews key determinants of demand and supply. A theoretical and empirical model of aggregate demand and supply of higher education is derived, with the aim to facilitate the understanding of the challenges in today's higher education systems, as well as the opportunities for development. The model is validated on some exemplary case studies describing different relationships between the level of public investment and levels of graduate population.